Analysis of Curriculum Policy Development and Implementation of Independent Curriculum in Elementary Schools - Fitriyani Fitriyani; Ira Restu Kurnia; Siska Nur Fadillah; Anna Maria Oktaviani (CV. Pusdikra Mitra Jaya, 2023)
This research is to find out and examine the